'Metal to resin': A comparative evaluation of conventional band and loop space maintainer with the fiber reinforced composite resin space maintainer in children - A Garg; F Samadi; J N Jaiswal; S Saha (Wolters Kluwer Medknow Publications, 2014)
Aims: To compare the clinical efficacy of two space maintainers namely, conventional band and loop and Fiber Reinforced Composite Resin (FRCR) space maintainers . Subjects and Methods: Thirty healthy children, aged 5 to 8 years were selected having at least two deciduous molars in different quadrants indicated for extraction or lost previously. FRCR space maintainer was placed in one quadrant and in the other quadrant band and loop space maintainer was cemented. All the patients were recalled at 1 st , 3 rd , and 6 th months for evaluation of both types of space maintainer. Patient acceptability, time taken, and clinical efficacy was recorded. Statistical analysis used: The observations thus obtained were subjected to statistical analysis using Chi- square test and Mann-Whitney U test. Results: Patient acceptability was greater in Group I (FRCR) in comparison to Group II (band and loop space maintainer). The time taken by Group I was significantly lower as compared to that of Group II. In Group I, debonding of enamel, composite was the most common complication leading to failure followed by debonding of fiber composite. In Group II, cement loss was the most common complication leading to failure followed by slippage of band and fracture of loop. The success rates of Groups I and Group II weares 63.3% and 36.7%, respectively. Conclusion: The study concluded that FRCRFiber Reinforced Composite Resin (Ribbond) space maintainers can be considered as viable alternative to the conventional band and loop space maintainers.